Getting innovation right how leaders leverage inflection points to drive success - Kahan, Seth (Gildan Audio, 2020)
Getting Innovation Right departs from the conventional wisdom of innovation, which 'encourages creativity, freewheeling experiments, tolerance for mistakes and failures, play, intuition, collaboration, curiosity, and so on. 'Play and curiosity are a wonderful part of everyday life and have their place in creating a culture of high performance, but they are not enough to drive results in the harsh realities of commerce. This book takes a hard-nosed stance and says, innovation is nothing if it is not successful. Here's what it takes to get traction and growth in the marketplace. A practical guide, this is the ultimate handbook for generating game-changing innovation in today's tumultuous economy, providing practicable guidance for an outcome-based approach to innovation that generates lasting value for clients. Kahan identifies the specific strategies that add value, including: introducing new ways of working, dealing successfully with disruption, coping with the down economy, responding to a revolutionary product sweeping through the marketplace and laying waste to existing industries.' Most crucially, he presents'a 7'step model for an innovation strategy that works: Discover Inflection Points Build Capacity Gather Business Intelligence Shift Perspective Exploit Disruption Generate Value Drive Uptake Getting Innovation Right will include stories, techniques, perspectives, and templates from the wide range of 60+ companies in diverse sectors where Kahan has led innovation initiatives. Innovation experts will contribute sidebars from their experience in the field. Grounded in real market experience, Getting Innovation Right is an indispensable resource for leaders looking to push the envelope in way that have the highest chance of success in the marketplace.